The effect of the alcohol content on the solubility of amino acids in aqueous solutions - Ferreira, Luísa (2010)
The solubility of me most simple a-amino acid, glycine, was measured in the temperature range between 25 and 60°C for the aqueous system of ethanol and at 25 °C for the aqueous system 0V 1-propanol. Theoretical work was essentially focused on the application of the excess solubility approach with conventional thermodynamic models such as the Margules and Wilson equations. The simple three suffix Margules model, with only one parameter to be estimated, gave the best results, with an average absolute deviation of 3.8%.